GLASS-BEARING XENOLITHS FROM CAPE VERDE: EVIDENCE FOR A HOT RISING MANTLE JET - Ryabchikov J.D.; Ntaflos T.; Kurat G.; Kogarko L.N. (My University, 1995)
Peridotitic xenoliths from melanephelinites of Sal Island, Cape Verde Archipelago, have a compositional range from moderately depleted Iherzolites to refractory harzburgites. Most xenoliths have protogranular textures but porphyroclastic and mylonitic textures are not uncommon. Small amounts of glass are present in the intergranular space of these rocks which possibly, at least in part, represent quenched silicate melt which invaded these rocks just before they were excavated. These glasses contain microphenocrysts of olivine, clinopyroxene, and spinel, as well as small grains of sulphides and metallic Fe-Ni alloys. Metallic phases were most likely produced by the desulphurization of sulfides, which also resulted in very low oxygen fugacities (several logarithmic units below QFM buffer) in the interstitial glasses and associated microphenocrysts. This is reflected in the chemical composition of the newly formed spinels which are characterised by low amounts of ferric iron. In contrast, primary spinel-bearing mineral assemblages of the peridotites were formed at much higher fO2. which were similar to those estimated for the host nephelinites which have high titanomagnetite contents.